A study on perception on the Malay language proficiency among Bangladeshi migrants who are involved in the business sector in Kuala Lumpur / Syed Abdul Razak Sayed Mahadi, Ain Shafiqah Mohd Nizan and Azhar Ab Wahab - Sayed Mahadi, Syed Abdul Razak; Mohd Nizan, Ain Shafiqah; Ab Wahab, Azhar (Universiti Teknologi MARA, 2021)
Malaysia whom with open arms welcomes foreigners to help develop its economy catches the attention of especially the Bangladeshis who are looking for opportunities. Undoubtedly, the presence of Bangladeshis has helped in filling in the vacancies in many sectors such as plantation, construction, services and manufacturing. Their work stint and experience gained leads to a paradigm shift, from an employee to an entrepreneur. Migration to Malaysia requires them to learn and acquire the Malay language for survival. In addition, proficiency in the Malay language is an added value as it makes them feel contented, secure and successful. This study aims to look at the perception on the proficiency of the Bangladeshi entrepreneurs who are adapting the Malay language as the main medium of communication. The relation between levels of education and proficiency in 1) speaking, 2) reading and 3) writing is analysed. This study also evaluates the importance of the Malay language usage among Bangladeshis in managing businesses. Taking a Mixed Methodology approach, a quantitative study was conducted using a questionnaire as a tool on 56 respondents who were selected using Purposive Sampling; while, qualitative method was used on 10 informants for in-Depth Interview on Bangladeshi migrants who were involved in business field around Kuala Lumpur. Surely, it is crucial for Bangladeshis who wish to work in this country to be proficient in the Malay language. This is to ensure their survival strategy is sustained, allowing them to tap a gold mine in Malaysian soil.